Mitochondrial sequence reveals high levels of gene flow between breeds of domestic sheep from Asia and Europe - Meadows, J. R. S.; Li, K.; Kantanen, J.; Tapio, M.; Sipos, W.; Pardeshi, V.; Gupta, V.; Calvo, J. H.; Whan, V.; Norris, B.; Kijas, J. W. (Journal of Heredity, 2005)
Sequence variation present within the mitochondrial genome was used to investigate genetic diversity within sheep breeds from Asia and Europe. Comparison of 2027 bp of sequence from 121 animals revealed 44 phylogenetically informative nucleotide positions and a single insertion/deletion. A total of 57 haplotypes were observed which formed two distinct clades. Type A haplotypes were found in breeds from Asia (India, Indonesia, Mongolia, and Tibet), while type B haplotypes were observed at the highest frequency in breeds sourced from Europe (nine breeds from Austria, angstrom land, Finland, Spain, and northwestern Russia). The distribution of haplotypes indicates sheep appear to have the weakest population structure and the highest rate of intercontinental dispersal of any domestic animal reported to date. Only 2.7% of the sequence variation observed was partitioned between continents, which is lower than both goat (approximately 10%) and cattle (approximately 50%). Diagnostic restriction fragment length polymorphism polymerase chain reaction (RFLP-PCR) tests which distinguish type A and B haplotypes were used to test an additional 223 animals from 17 breeds of European and Asian origin. A mixture of the two lineages was found in every breed except Suffolk and the Indian Garole, indicating introgression has played a major part during breed development and subsequent selection.

QTL mapping of 1000-kernel weight, kernel length, and kernel width in bread wheat (Triticum aestivum L.) - Ramya, P.; Chaubal, A.; Kulkarni, K.; Gupta, L.; Kadoo, Narendra Y.; Dhaliwal, Harcharan Singh; Chhuneja, Parveen; Lagu, Meena D.; Gupta, V. (Journal of Applied Genetics, 2010)
Kernel size and morphology influence the market value and milling yield of bread wheat (Triticum aestivum L.). The objective of this study was to identify quantitative trait loci (QTLs) controlling kernel traits in hexaploid wheat. We recorded 1000-kernel weight, kernel length, and kernel width for 185 recombinant inbred lines from the cross Rye Selection 111 x Chinese Spring grown in 2 agro-climatic regions in India for many years. Composite interval mapping (CIM) was employed for QTL detection using a linkage map with 169 simple sequence repeat (SSR) markers. For 1000-kernel weight, 10 QTLs were identified on wheat chromosomes 1A, 1D, 2B, 2D, 4B, 5B, and 6B, whereas 6 QTLs for kernel length were detected on 1A, 2B, 2D, 5A, 5B and 5D. Chromosomes 1D, 2B, 2D, 4B, 53 and 5D had 9 QTLs for kernel width. Chromosomal regions with QTLs detected consistently for multiple year-location combinations were identified for each trait. Pleiotropic QTLs were found on chromosomes 2B, 2D, 4B, and 5B. The identified genomic regions controlling wheat kernel size and shape can be targeted during further studies for their genetic dissection.
Keywords: composite interval mapping; kernel shape; kernel size; quantitative trait loci; Stable QTLs; Triticum aestivum